CAD/CAMTechnology:ABoontoApparellndustry - Kaur , Prabhjot (Gyan Management Journal, 2011)
Globalization, availability of information and advanced communications systems have changed profoundly the face of Apparel industry and have simultaneously stimulated competition. Though manufacturers offer unlimited designs but the basic problem remains as to how to bring such designed products to market quickly and release market updates. This problem has been rectified by Computer Aided Designing and Computer Aided manufacturing systems which are now the essential tools required to integrate and achieve success taking the role of the Designer. The objective of this paper is to spread awareness regarding the use of different CAD and CAM systems and how they help in giving suppliers and exporter's edge over to get recurrent orders and to enhance production in Apparel fashion industry. Different CAD systems available in India are body measurement, body scanning, digitizing, grading, marker making, pattern design and generation, texture and embroidery, design specifications, cost, data management and 3D visual merchandising systems using software's like Gerber, Tukatech, Lectra, Adobe Photoshop, Core/Draw, Illustrator, Digital Fashion Pro, Wilcom etc. Some of them are being used in various departments i.e. Design, Production and Sales in Ludhiana readymade garment manufacturing units. New Technology is being integrated with traditional methods as manufacturers are still hesitant to totally depend on it. Punjab Government has taken initiative for technological up gradation by offering different schemes but still lot needs to be done. Some more efforts are required for smooth infusion and diffusion of CAD/CAM technology in Ludhiana Apparel industry which had revolutionized the whole garment manufacturing process.
Keywords: SWOT Analysis; Challenges; CAD systems; Digital Fashion; Body Scanning; 3D Fit